The Insight in Traditional and Innovative Aging Technologies: Influence on Quality and Consumer Preferences of Aged Spirits: Insight in Traditional and Innovative Aging Technologies - Krstić, Jelena; Kostić-Stanković, Milica; Veljović, Sonja (Journal of Agricultural Sciences (Belgrade), 2021)
Aging is one of the most important processes in the production of high-quality spirits, including whisky, brandy and cognac. The contact between wood and distillate is a crucial step for the migration of chemical compounds, which evoke the novel sensory properties of the final products. Novel taste is pleasurable for a very broad group of consumers and depends on cultural preferences. In order to demystify the main chemical compounds for aroma contribution, connecting them with a sensory profile of aged spirits is a crucial step in hastening the very timeless process, without quality decreasing. Consumption patterns of alcohol spirits have been influenced by changed consumers’ preferences and an increased availability of different types of spirits on the market. Consumers’ choice of one type of alcohol spirit over others is significantly shaped by extrinsic attributes and consumer-based factors, but the choice among different available options of the single type of spirit, may be based on consumers’ perception of its specific sensory attributes. Therefore, the combination of taste, aroma, color and other sensory attributes of an alcohol spirit can shape consumers’ perceived quality of the spirit and impact the potential of its market success in general.